On the new wave behavior to the Klein-Gordon-Zakharov equations in plasma physics - Baskonus, H. M.; Sulaiman, T. A.; Bulut, H. (Indian Assoc Cultivation Science, 2019)
In this study, the extended sinh-Gordon equation expansion method is used in constructing various exact solitary wave solutions to the Klein-Gordon-Zakharov equations. The Klein-Gordon-Zakharov equations is a nonlinear model describing the interaction between the Langmuir wave and the ion acoustic wave in a high-frequency plasma. We successfully construct some topological, non-topological, compound topological and non-topological, singular, compound singular solitons and singular periodic wave solutions. Under the choice of suitable values of the parameters, the 2D, 3D and contour graphs to some of the reported solutions are also plotted.
Keywords: The ShGEEM; Klein-Gordon-Zakharov equations; Plasma physics; Wave solutions